Cultural and Religious Tensions in Dealing with the Covid-19 Pandemic: A Study of the Meujalateh Ritual in Ie Itam Baroh, Woyla, West Aceh: Tensi Budaya dan Agama dalam Menghadapi Pandemi Covid-19: Studi Ritual Meujalateh Masyarakat Ie Itam Baroh, Woyla, Aceh Barat - Idria, Reza; Thalal, Muhammad (Indonesian Journal of Islamic History and Culture, 2025)
The COVID-19 pandemic has reignited the practice of religious rituals in Indonesia as a means to respond to the spread of the virus. One notable example is the Meujalateh ritual performed by the Woyla community in West Aceh, aimed at "warding off" the coronavirus. While some perceive this ritual as a religious practice rooted in Islamic teachings, others consider it a customary tradition. This study frames Meujalateh as part of the oral tradition of the Acehnese people. By using the oral tradition paradigm, this research explores the cultural and communal significance of the ritual, highlighting its value as an intangible cultural heritage that should be preserved, developed, and utilized for future generations.